2000
DOI: 10.22358/jafs/68054/2000
|View full text |Cite
|
Sign up to set email alerts
|

Metabolisable energy value of rapeseed meal and its fractions for chickens as affected by oil and fibre content

Abstract: Low glucosinolate rapeseed meal (RM) was separated on sieves of 150, 270 and 450 pm diameter into 3 fractions defined as flour, bran and hulls. The fractions and rape seed oil were mixed in different proportions in order to obtain 25 model rapeseed meals differing in crude fibre 8.8, 10.3, 11.8, 13.2 and 14.7% DM and in crude fat 4.3, 6.3, 8.2, 10.2 and 12.1% DM (two-factorial design).The digestibility of nutrients and apparent metabolisable energy (AME N ) of RM, fractionated material and model RMs was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…The use of large amounts of RSM is limited because of the lower energy and higher fi bre contents compared with SBM. The crude fi bre content of RSM negatively affected the AMEn value for broiler chickens (Chibowska et al, 2000). These fi ndings are in agreement with those showing that the inclusion of high levels of CM in broiler diets have adverse effects on broiler chickens performance (Tripathi and Mishra, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The use of large amounts of RSM is limited because of the lower energy and higher fi bre contents compared with SBM. The crude fi bre content of RSM negatively affected the AMEn value for broiler chickens (Chibowska et al, 2000). These fi ndings are in agreement with those showing that the inclusion of high levels of CM in broiler diets have adverse effects on broiler chickens performance (Tripathi and Mishra, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…One of the reasons for reduced broilers BW gain between 1 to 21 d may be due to a higher crude fiber content of diets that containing 20% CM, which may be negatively affected AME n value for broiler chickens (Chibowska et al, 2000). Another of the reasons for reduced broilers BW gain between 1 to 21 d probably due to higher NSP content of CM as compared with SBM.…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be concluded that fractionation did not give the expected benefits. Chibowska et al (2000) found, moreover, that lowering the level of fibre and increasing the share of protein in rapeseed meal by mechanical separation is a costly and economically unjustified process. Rotkiewicz and Zadernowski (1997) believe that it would be more beneficial to remove the seed coat of rapeseed before oil is pressed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rapeseed meal in the nutrition of broilers is more common (Smulikowska et al, 1991(Smulikowska et al, , 1998Chibowska et al, 2000;Kamińska et al, 2000), than in laying hens (Rutkowski et al, 1989;Gwara et al, 1993;Brettschneider et al, 1995;Niemiec et al, 2001). This may be caused by the occurrence of the unpleasant "fishy" odour of eggs from some hens fed rapeseed meal.…”
Section: Introductionmentioning
confidence: 99%